The mineralized veins and the impact of old mine workings on the environment at Segura, central Portugal - Antunes, I.M.H.R. (2013)
At Segura, granitic pegmatite veins with cassiterite and lepidolite, hydrothermal Sn–W quartz veins and Ba–Pb–Zn quartz veins intruded the Cambrian schist–metagraywacke complex and Hercynian granites. Cassiterite from Sn–W quartz veins is richer in Ti and poorer in Nb and Nb + Ta than cassiterite from granitic pegmatite. Wolframite from Sn–W quartz veins is enriched in ferberite component. The Sn–W quartz veins contain pyrrhotite, arsenopyrite, sphalerite, chalcopyrite, stannite, matildite and schapbachite and the Ba–Pb–Zn quartz veins have cobaltite, pyrite, sphalerite, chalcopyrite, galena and barite, which were analyzed by electron microprobe. The presently abandoned mining area was exploited for Sn, W, Ba and Pb until 1953. Stream sediments and soils have higher concentrations of metals than parent granites and schists. Sn, W, B, As and Cu anomalies found in stream sediments and soils are associated with Sn–W quartz veins, while Ba, Pb and Zn anomalies in stream sediments and soils are related to Ba–Pb–Zn quartz veins. Sn, W, B, As, Cu, Ba, Pb and Zn anomalies in stream sediments and soils are also related to the respective old mining activities, which increased the mobility of trace metals from mineralized veins to soils, stream sediments and waters. Stream sediments and soils are sinks of trace elements, which depend on their contents in mineralized veins and weathering processes, but Sn, Wand B depend mainly on a mechanic process. Soils must not be used for agriculture and human residence due to their Sn, B, As and Ba contents. Waters associated with mineralized veins were analyzed by flame atomic absorption spectroscopy (FAAS) and ICP-AES have high As, Fe and Mn and should not be used for human consumption and agriculture activities. The highest As values in waters were all related to Sn–W quartz veins and the highest Fe and Mn values were associated with the Ba–Pb–Zn quartz veins. No significant acid drainage was found associated with the old mine workings.